As tecnologias no ensino remoto: uma abordagem sobre a contribuição do smartphone nas aulas de matemática - Spatti, José Adriano (2022)
Technology can contribute to the teaching process and is considered a means for learning to occur. Taking into account the pandemic situation that affected the world in 2020, this dissertation presents the result of an exploratory and reflective study whose objective was to identify aspects that implied in the practice of the mathematics teacher in the face of remote teaching - considered by the authorities as a emerging solution to preserve people's health - causing profound changes in the educational scenario through a teaching format unknown until then. To facilitate and assist this confrontation, the use of digital technologies has become indispensable to guarantee the learning of students, especially in Mathematics. This scientific research, whose methodology will be a bibliographic review and content analysis by Bardin, meets this need to reflect on the use of the smartphone as an emerging resource with great access to the general population, contextualizing its use as a resource that facilitates learning, bringing their contributions and also the weak points within the educational process, providing an opportunity to reflect on the importance of diversifying pedagogical practices, which required a new look at education itself. In this sense, it is necessary to include all the actors involved in the study: students, teachers and the school community, so that technological innovation goes beyond the issue of methodological practice, so that cultural and social aspects can also be experienced. The great differential shown, however, will be the increment of new ways of presenting mathematics to students using the smartphone as an innovative resource. The Google Scholar, Scielo and Web of Science platforms were used to survey the works, restricting the temporality between the years 2020 and 2022. The 72 results obtained in the bibliographic survey were categorized through the following aspects: Potentialities, Weaknesses; Content Involved; Intentionality; Applications Used and Results Obtained. There is no way to despise the smartphone. He has already become a partner for work, studies and also for leisure of both subjects involved in the educational process. It is necessary to look at the possibilities of contribution of the device as an enabling tool, in the contribution of learning, from other angles, and it is up to educators to guide students in the conscious use of this technology, which has gone from villain to protagonist in this scenario of remote teaching.